Preoperative nTMS-based mapping of a verbal semantic association task allows for the identification of extensive bihemispheric cortical and subcortical networks - Schwendner, Maximilian; Kram, Leonie; Zhang, Haosu; Krieg, Sandro; Ille, Sebastian (Journal of neuro-oncology, 2026)
Purpose: Accurately mapping higher cognitive functions remains a challenge both intraoperatively and preoperatively. This study is the first to preoperatively evaluate the bihemispheric cortical and subcortical networks by preoperative nTMS-based mapping of a verbal semantic association task, based on the intraoperatively established Pyramids and Palm Trees Test (PPTT). Methods: The PPTT was integrated into the established workflow of preoperative nTMS-based mapping. Fibertracking (FT) was performed using a fractional anisotropy (FA) threshold set at 50% of the maximum FA and a minimum fiber length (FL) of 100 mm. Results: The study included 20 patients with right-sided gliomas. Overall error rates in the lesional (right) hemisphere were 0.108 ± 0.053, compared to 0.098 ± 0.047 in the contralateral (left) hemisphere (p = 0.215). Semantic errors were observed more frequently in the right hemisphere (right: 0.0275 ± 0.015, left: 0.016 ± 0.015; p = 0.01). Tractography-based network analysis demonstrated comparable network properties regarding fiber volumes (left: 36 ± 16 (14–83) cm3, right: 33 ± 15 (9–65) cm3; p = 0.492), fiber lengths (left: 120 ± 10 (106–140) mm, right: 116 ± 9 (105–144) mm; p = 0.185)) and mean FA values (left: 0.37 ± 0.04 (0.32–0.45), right: 0.37 ± 0.04(0.25–0.41); p = 0.353) between hemispheres. Conclusion: The PPTT, when used as a verbal semantic association task, enables a function-based identification of the bihemispheric network underlying semantic association and complex language processing. Function-based FT revealed an extensive right-hemispheric network, comparable in volume, mean FA and fiber length to the left hemisphere. These findings suggest that bihemispheric networks are crucial in higher cognitive functions, including semantic processing during complex language tasks. Clinical trial number: The trial was registered on clinicaltrials.gov (NCT06401057) on January 7th 2024.